2009
DOI: 10.1073/pnas.0812074106
|View full text |Cite
|
Sign up to set email alerts
|

Host cell-free growth of the Q fever bacterium Coxiella burnetii

Abstract: The inability to propagate obligate intracellular pathogens under axenic (host cell-free) culture conditions imposes severe experimental constraints that have negatively impacted progress in understanding pathogen virulence and disease mechanisms. Coxiella burnetii, the causative agent of human Q (Query) fever, is an obligate intracellular bacterial pathogen that replicates exclusively in an acidified, lysosome-like vacuole. To define conditions that support C. burnetii growth, we systematically evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
386
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 363 publications
(399 citation statements)
references
References 36 publications
6
386
0
7
Order By: Relevance
“…Reduced oxygen tension is critical for axenic replication of the obligate intracellular parasite Coxiella burnetii (28). Similarly, C. trachomatis encodes cytochrome bd, a terminal oxidase with increased affinity for oxygen and thus associated with metabolic activity under reduced oxygen conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced oxygen tension is critical for axenic replication of the obligate intracellular parasite Coxiella burnetii (28). Similarly, C. trachomatis encodes cytochrome bd, a terminal oxidase with increased affinity for oxygen and thus associated with metabolic activity under reduced oxygen conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Coxiella burnetii Nine Mile Phase II, strain RSA 439, was cultured axenically in acidified citrate cysteine media 2 (ACCM-2; made in-house) as previously described [40]. When required, chloramphenicol (Boehringer Mannheim, 634,433) and/or kanamycin (Amresco, 0408) were added to ACCM-2 at 3 µg/ml and 300 µg/ml respectively.…”
Section: Methodsmentioning
confidence: 99%
“…C. burnetii Nine Mile phase II (clone 4, RSA439) was cultured axenically in ACCM-2 as previously described (12,16). E. coli TOP10 and BL21-AI (Invitrogen) were grown in Luria-Bertani medium for recombinant DNA procedures and protein purification.…”
Section: Methodsmentioning
confidence: 99%
“…C. burnetii encodes a Dot/Icm type 4B secretion system (T4BSS) homologous to the T4BSS of L. pneumophila (14). Recent advances in C. burnetii host-cell-free culture (12) and genetic manipulation (15) have enabled confirmation that type 4B secretion is essential for productive infection. Himar1 transposon mutagenesis revealed that icmL and icmD are required for translocation of effectors and colonization of host cells (16,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation